Analysis of Factors Affecting Customer Loyalty and Acquisition in Sociopreneurship-Based Cleaning Services - Ratih Dwi Amalia; Eko Ruddy Cahyadi; Elisa Anggraeni (Indonesian Journal of Business Analytics, 2024)
The competitive landscape necessitates that startups have competitive strategies to attract consumers and retain customers. Startups need to realize sustainable business practices where companies cannot solely focus on profit but also implement sustainable business concepts that consider social and economic dimensions. Various digital platforms can be utilized by companies to publicize their business activities. One such startup that applies this strategy is Cleansheet, a sociopreneurship in the field of cleaning service based on empowerment. The research was conducted in Bogor from January to March 2024 through interviews and the distribution of questionnaires to 285 respondents. The results of the SEM analysis show that Cleansheet's customer acquisition is significantly influenced by digital marketing, customer loyalty, and sustainability perception. Meanwhile, customer loyalty is significantly influenced by customer satisfaction, sustainability perception, digital marketing, and service quality. Regarding the indirect effect, customer satisfaction significantly acts as a mediating variable in the partial influence of digital marketing and service quality on customer loyalty.